Evaluation of the Environmental Performance of Residential Building Envelope Components - Tokbolat, Serik; Nazipov, Farnush; Kim, Jong; Karaca, Ferhat (MDPI, 2019)
The role of buildings in the context of addressing the consequences of climate change and the energy deficit is becoming increasingly important due to their share in the overall amount of green house gas (GHG) emissions and rapidly growing domestic energy consumption worldwide. Adherence to a sustainability agenda requires ever-increasing attention to all stages of a building0 s life, as such approach allows for the consideration of environmental impacts of a building, from design, through construction stages, until the final phase of a building0 s life—demolition. A life cycle assessment (LCA) is one of the most recognized and adopted models for the evaluation of the environmental performance of materials and processes. This paper aims to perform an LCA of four different types of residential buildings in Nur-Sultan, Kazakhstan. The assessment primarily considered embodied energy and GHG emissions as key assessment indicators. Findings suggest that the operational stage contributed to more than half of the GHG emissions in all the cases. The results of the study indicate that there is a dependence between the comfort levels and the impact of the buildings on the environment. The higher the comfort levels, the higher the impacts in terms of the CO2 equivalent. This conclusion is most likely to be related to the fact that the higher the comfort level, the higher the environmental cost of the materials. A similar correlation can be observed in the case of comparing building comfort levels and life-cycle impacts per user. There are fewer occupants per square meter as the comfort level increases. Furthermore, the obtained results suggest potential ways of reducing the overall environmental impact of the building envelope components.